Graphics programming in C : a comprehensive resource for every C programmer : covers CGA, EGA, and VGA graphic displays and includes a complete toolbox of graphic routines and sample programs - Stevens, Roger T. (California : M&T Publishing, Inc., 1988)
The purpose of this book to present all of the information that you need to do graphics programming in the C language the functions of the color/grphics adapter (CGA), the hercules graphics card, the enhanced graphics adapter (EGA), and the video graphics array (VGA) are all described in sufficient detail to permit you to program direct interface with them.
Chapter 1. Introduction -- Chapter 2. graphics and the C language -- Chapter 3. The color/graphics adapter and the hercules graphics card-- Chapter 4. The enhanced graphics adapter and the video graphics array -- Chapter 5. ROM BIOS video services -- Chapter 6. Using the ROm BIOS video services with C -- Chapter 7. Graphics functions for the hercules graphics card -- Chapter 8. Displaying a point on the screen -- Chapter 9. Coordinate systems and clipping boundaries -- Chapter 10. Drawing lines and rectangles -- Chapter 11. Drawing ovals, circles and arcs -- Chapter 12. Drawing rounded rectangles and polygons -- Chapter 13. Drawing bezier and B-spline curves -- Chapter 14. Translation and rotation -- Chapter 15. Generating graphics and cursors -- Chapter 16. Using text in graphics displays -- Chapter 17. Pop-up windows and menus -- Chapter 18. Three-dimensional drawing -- Chapter 19. Shading three-dimensional figures -- Chapter 20. Creating a graphics library -- Chapter 21. Demonstration programs -- Chapter 22. Printing graphics displays -- Chapter 23. Fractals: the face o fthe future.
Includes bibliographical references and index.
Keywords: C (COMPUTER PROGRAM LANGUAGE)